A systematic review of the effect of rearing substrate composition on the fatty acid profile of black soldier fly larvae (Hermetia illucens) - Gleeson, Elizabeth Yvonne (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.